India Development Update, March 2018 : India's Growth Story - World Bank (World Bank, Washington, DC, 2018)
India has achieved much in the last 25 years. Since the early 1990s, when reforms began, growthrates have been higher and more stable, the economy has become more modern and globally integrated,macroeconomic stability has improved, and the average citizen is better educated and lives longer. In addition, the business environment and governance standards have improved, there is political stability, and the geopolitical environment is relatively stable. Yet an economic deceleration in the last few quarters has generated worried commentaries about India's growth potential. The questions being raised are: Is the deceleration in economic growth structural or cyclical? Is the Indian growth story over? What is the "new normal" for India's growth potential? What sets of policies, structural or cyclical, might be needed to revive growth? In this report, we take a long-term perspective on India's growth outlook. Looking back at the last 50 years, we note that India's average growth has accelerated slowly but steadily across sectors--agriculture, industry and services ---and become more stable. This is reflected in increasing labor productivity and total factor productivity.